Naloxone fails to antagonize initial hypoalgesic effect of a manual therapy treatment for lateral epicondylalgia. - Paungmali A; O'Leary S; Souvlis T; Vicenzino B (Journal of Manipulative & Physiological Therapeutics)
BACKGROUND: Recent research has shown that Mulligan's Mobilization With Movement treatment technique for the elbow (MWM), a peripheral joint mobilization technique, produces a substantial and immediate pain relief in chronic lateral epicondylalgia (48% increase in pain-free grip strength).([1]) This hypoalgesic effect is far greater than that previously reported with spinal manual therapy treatments, prompting speculation that peripheral manual therapy treatments may differ in mechanism of action to spinal manual therapy techniques. Naloxone antagonism and tolerance studies, which employ widely accepted tests for the identification of endogenous opioid-mediated pain control mechanisms, have shown that spinal manual therapy-induced hypoalgesia does not involve an opioid mechanism. OBJECTIVE: The aim of this study was to evaluate the effect of naloxone administration on the hypoalgesic effect of MWM. METHODS: A randomized, controlled trial evaluated the effect of administering naloxone, saline, or no-substance control injection on the MWM-induced hypoalgesia in 18 participants with lateral epicondylalgia. Pain-free grip strength, pressure pain threshold, thermal pain threshold, and upper limb neural tissue provocation test 2b were the outcome measures. RESULTS: The results demonstrated that the initial hypoalgesic effect of the MWM was not antagonized by naloxone, suggesting a nonopioid mechanism of action. CONCLUSIONS: The studied peripheral mobilization treatment technique appears to have a similar effect profile to previously studied spinal manual therapy techniques, suggesting a nonopioid-mediated hypoalgesia following manual therapy.